2018
DOI: 10.1016/j.ijsu.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Conversion surgery for gastric cancer: A cohort study from a western center

Abstract: Conversion gastrectomy, when R0 could be achieved, is associated with long survivals and it is the most important prognostic factor in patients with advanced gastric cancer. Further studies are needed to define the ideal patient who can really benefit from this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…Patients who underwent R0 resection had an MST of 41.3 mo[ 84 ]. Recently, Morgagni et al[ 85 ] reported a Western series of 22 patients among 73 unresectable subjects who underwent R0 resection after induction chemotherapy. Gastrectomy plus HIPEC was performed in 9 patients.…”
Section: From Salvage Surgery To Conversion Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who underwent R0 resection had an MST of 41.3 mo[ 84 ]. Recently, Morgagni et al[ 85 ] reported a Western series of 22 patients among 73 unresectable subjects who underwent R0 resection after induction chemotherapy. Gastrectomy plus HIPEC was performed in 9 patients.…”
Section: From Salvage Surgery To Conversion Therapymentioning
confidence: 99%
“…Gastrectomy plus HIPEC was performed in 9 patients. The 1- and 3-year survival rates were 63.6% and 39.4%, respectively[ 85 ].…”
Section: From Salvage Surgery To Conversion Therapymentioning
confidence: 99%
“…According to the ToGA trial, the median OS was observed to extend to 13.8 months following trastuzumab therapy [2]. On the other hand, recent studies have shown the prognostic benefit of conversion surgery after chemotherapy in patients with unresectable gastric cancer [12][13][14][15][16][17][18][19]. Especially, some reports suggested prognostic importance of R0 resection after palliative chemotherapy in conversion surgery of stage IV gastric cancer patients who responded to the chemotherapy [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for those undergoing systemic therapies only for gastric cancers who were either initially diagnosed as metastatic or having developed recurrence after initial curative resection was dismal, in spite of recent advancements made in targeted and immune-based therapies [3]. Accordingly, there have been attempts to proceed to conversion surgery in metastatic gastric cancer in an effort to add survival benefit to chemotherapy even when systemic treatment only could at least temporarily control the microscopic disease [4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Conversion surgery is a term for operative resection of primary or metastatic lesions with a curative intent, after confirming either a complete response (CR) or partial response (PR), following several cycles of palliative chemotherapy. Although addition of gastrectomy (without metastasectomy) to palliative chemotherapy in metastatic gastric cancer did not show survival benefit when compared with chemotherapy only in the previous REGATTA trial [4], there have been recent attempts to conduct surgery in selected patients with a good initial response to palliative chemotherapy [5][6][7][8][9][10][11][12]. It has been shown to improve the prognosis in a few retrospective studies.…”
Section: Introductionmentioning
confidence: 99%